Randomised clinical trial: alisporivir combined with peginterferon and ribavirin in treatment‐naïve patients with chronic HCV genotype 1 infection (ESSENTIAL II). Issue 7 (4th August 2015) - Zeuzem, S.; Flisiak, R.; Vierling, J. M.; Mazur, W.; Mazzella, G.; Thongsawat, S.; Abdurakhmanov, D.; Van Kính, N.; Calistru, P.; Heo, J.; Stanciu, C.; Gould, M.; et al.
Summary Background Alisporivir (ALV) is an oral, host‐targeting agent with pangenotypic anti‐hepatitis C virus (HCV) activity and a high barrier to resistance. Aim To evaluate efficacy and safety of ALV plus peginterferon‐α2a and ribavirin (PR) in treatment‐naïve patients with chronic HCV genotype 1 infection. Methods Double‐blind, randomised, placebo‐controlled, Phase 3 study evaluating ALV 600 mg once daily [response‐guided therapy (RGT) for 24 or 48 weeks or 48 weeks fixed duration] or ALV 400 mg twice daily RGT with PR, compared to PR alone. Following a Food and Drug Administration partial clinical hold, ALV/placebo was discontinued and patients completed treatment with PR only. At that time, 87% of patients had received ≥12 weeks and 20% had received ≥24 weeks of ALV/PR triple therapy. Results A total of 1081 patients were randomised (12% cirrhosis, 55% CT/TT IL28B). Addition of ALV to PR improved virological response in a dose‐dependent fashion. Overall, sustained virological response (SVR12; primary endpoint) was 69% in all ALV groups vs. 53% in PR control. Highest SVR12 (90%) was achieved in patients treated with ALV 400 mg twice daily and PR for >24 weeks. Seven cases of pancreatitis were reported, with similar frequency between ALV/PR and PR control groups (0.6% vs. 0.8% respectively). Adverse events seen more frequently with ALV/PR than with PR alone were anaemia, thrombocytopenia, hyperbilirubinaemia and hypertension. Conclusions Alisporivir, especially the 400 mg twice daily regimen, increased efficacy of PR therapy in treatment‐naïve patients with HCV genotype 1 infection. The mechanism of action and pangenotypic activity suggest that alisporivir could be useful in interferon‐free combination regimens.